2021
DOI: 10.1038/s41598-021-84184-y
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant vascular-targeted photodynamic therapy improves survival and reduces recurrence and progression in a mouse model of urothelial cancer

Abstract: Locally advanced urothelial cancer has high recurrence and progression rates following surgical treatment. This highlights the need to develop neoadjuvant strategies that are both effective and well-tolerated. We hypothesized that neoadjuvant sub-ablative vascular-targeted photodynamic therapy (sbVTP), through its immunotherapeutic mechanism, would improve survival and reduce recurrence and progression in a murine model of urothelial cancer. After urothelial tumor implantation and 17 days before surgical resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…This innovative treatment approach's principle relies on generating a versatile mix of ROS/RNS species capable of eliciting oxidative distress and thereby lethal damage in tumor cells. This concept is comparable to photodynamic therapy (PDT) that has already been implemented for many types of cancer therapies in clinical oncology [26] and is also under investigation for its usage in the treatment of urinary bladder cancer [27] , [28] . However, knowledge of the efficacy of the multi-ROS/RNS mixtures of medical gas plasma technology against this disease is rare.…”
Section: Discussionmentioning
confidence: 99%
“…This innovative treatment approach's principle relies on generating a versatile mix of ROS/RNS species capable of eliciting oxidative distress and thereby lethal damage in tumor cells. This concept is comparable to photodynamic therapy (PDT) that has already been implemented for many types of cancer therapies in clinical oncology [26] and is also under investigation for its usage in the treatment of urinary bladder cancer [27] , [28] . However, knowledge of the efficacy of the multi-ROS/RNS mixtures of medical gas plasma technology against this disease is rare.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional PDT is based on intravenous infusion of a photosensitizer followed by light illumination [ 26 , 27 ]. This causes a localized ischemia-reperfusion injury [ 28 , 29 ] or a direct tissue injury [ 30 , 31 ] depending on photosensitizer localization. In contrast to traditional PDT, the developed technique involves a local infusion of the photosensitizer into the renal pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have examined combinations of vascular-targeted PDT with WST11 [42][43][44]. Corradi et al showed very interesting results for the combination with anti-CTLA4 immunotherapy in a heterotopic urothelial carcinoma mouse model: significantly reduced tumor growth, reduced development of lung metastases, prolonged survival, and no tumor growth after tumor re-irradiation in pretreated mice [42].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Alvim et al recently published further data on vascular-targeted PDT (WST 11) in combination with a PD1 inhibitor and OX40 in a mouse model with allografted MB-49 upper tract urothelial carcinoma cells. The above combination therapy showed the best efficacy in inhibiting tumor growth and prolonging survival compared to the combination with only one of the above agents [44]. Poly(caprolactone) based biodegradable and nontoxic polymeric matrix was used to formulate an in situ thermo-responsive hydrogel to deliver doxorubicin [45].…”
Section: In Vivo Studiesmentioning
confidence: 99%